Zero-forcing decision-feedback equalizer for packet data transmission - Kawas Kaleh, G. (IEEE International Conference on Communications, 1993, 1993)
For communication over channels subject to fast time-variation, e.g., the HF channel, the information symbols are arranged in the form of blocks separated by known symbols. The known receiver for this system is the nonlinear data-directed estimator (NDDE). An appropriate zero-forcing decision-feedback equalizer which has better performance and lower complexity is derived. Whereas the NDDE uses the Levinson algorithm to solve M/2 Toeplitz systems of decreasing order (where M is the number of symbols per block), the author's equalizer needs to process only one Toeplitz system. The Schur algorithm, proposed for Cholesky factorization, allows further reduction in the complexity of the process.< >